2017
DOI: 10.3748/wjg.v23.i41.7425
|View full text |Cite
|
Sign up to set email alerts
|

Value of gamma-glutamyltranspeptidase-to-platelet ratio in diagnosis of hepatic fibrosis in patients with chronic hepatitis B

Abstract: AIMTo investigate the value of the gamma-glutamyltraspeptidase (GGT)-to-platelet (PLT) ratio (GPR) in the diagnosis of hepatic fibrosis in patients with chronic hepatitis B (CHB).METHODSWe included 390 untreated CHB patients in this study. The GPR, aspartate aminotransferase (AST)-to-PLT ratio index (APRI), and fibrosis-4 (FIB-4) of all patients were analysed to determine if these parameter were correlated with age, gender, medical history, liver function [total bilirubin (TBil), alanine aminotransferase (ALT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
20
2
1
Order By: Relevance
“…It is considered in the risk assessment of liver fibrosis that both AST and ALT may remain normal even in cirrhosis situations (Newsome et al, 2018). GGT, in turn, is considered a serum predictor of histopathological evolution (Hu et al, 2017). However, in the present study, the high prevalence of individuals with no liver parenchymal abnormalities is suggested in the lack of association between GGT and fibrosis.…”
Section: Discussioncontrasting
confidence: 53%
“…It is considered in the risk assessment of liver fibrosis that both AST and ALT may remain normal even in cirrhosis situations (Newsome et al, 2018). GGT, in turn, is considered a serum predictor of histopathological evolution (Hu et al, 2017). However, in the present study, the high prevalence of individuals with no liver parenchymal abnormalities is suggested in the lack of association between GGT and fibrosis.…”
Section: Discussioncontrasting
confidence: 53%
“…In line with some recent reports, our studies have found that the AUROC for the GPR in F1 to F4 stages was significantly higher than those for FIB-4 index and APRI. [28][29][30] The study was mainly limited by the small proportion of samples that were F4 (6.3%). In addition, we were not able to test the influence of a high ALT level as we had excluded patients with an ALT of 5 × ULN or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences showed that several inflammatory cytokines, including tumor necrosis factor α, interferon-α, and interferon-β, could induce GGT expression [ 45 , 46 ]. Additionally, it was also reported that serum GGT level associates with the active status, fibrosis and cirrhosis stage of chronic hepatitis [ 51 , 52 ] and functions as a biomarker of the inflamed liver microenvironment in hepatitis [ 53 ]. Therefore, it may be hypothesized that GGT reflects or participates in the tumor-associated inflammatory responses to predict the prognosis of tumor patients.…”
Section: Discussionmentioning
confidence: 99%